EBI2-oxysterol signalling regulates VE-cadherin expression and multiple sclerosis CD4+ T cell attachment to a human tri-cell spheroid blood-brain barrier model - Fionä Caratis; Inez Mruk; Klaudia Konieczna-Wolska; Bartłomiej Rojek; Marek Hałas; Paulina Czaplewska; Bartosz Karaszewski; Tomomi Furihata; Aleksandra Rutkowska (Brain, Behavior, & Immunity - Health)
Changes in the function of the blood-brain barrier (BBB) are one of the hallmarks of multiple sclerosis (MS) and are observed at very early stages of the disease. Several disease-modifying therapies for MS regulate tight junction and adherence junction proteins in the BBB thus limiting the entry of peripheral immune cells into the central nervous system (CNS). The Epstein-Barr virus-induced gene 2 (EBI2) was shown to drive immune cell migration towards high concentration of its endogenous ligand, oxysterol 7α,25OHC, which concentrations increase during inflammation in the CNS. Here, the data showed upregulated transcripts of EBI2 and CH25H, the first enzyme in 7α, 25OHC synthesis pathway, in MS brain lesions. In vitro, cerebrospinal fluid (CSF) from patients with MS downregulated HSD3B7, the 7α, 25OHC degrading enzyme, and VE-cadherin levels in the tri-cell human BBB spheroid model. Importantly, EBI2 signalling mediated the attachment of MS patient-derived CD4+ T cells to the BBB spheroids. The data raises the possibility that elevated oxysterol levels in an inflamed brain might trigger a downregulation of VE-cadherin in endothelial cells, potentially easing the CNS infiltration of EBI2-expressing immune cells. This process can be modulated through the use of EBI2 ligands, suggesting a potential pathway for therapeutic intervention.